Study of intersubband transitions in Si1-xGex/Si quantum wells using 14-band k⋅p model - Liu, W.; Zhang, D. H.; Loh, T. H.; Yoon, S. F.; Balasubramanian, N. (Universiti Malaysia Perlis, 2008)
Link to publisher's homepage at http://www.unimap.edu.my/ ; Open access only applicable for vol. 1; issue 1, 2008.